2013
DOI: 10.1155/2013/538017
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Activation Microparticles and Inflammation Status Improve with Exercise Training in African Americans

Abstract: African Americans have the highest prevalence of hypertension in the world which may emanate from their predisposition to heightened endothelial inflammation. The purpose of this study was to determine the effects of a 6-month aerobic exercise training (AEXT) intervention on the inflammatory biomarkers interleukin-10 (IL-10), interleukin-6 (IL-6), and endothelial microparticle (EMP) CD62E+ and endothelial function assessed by flow-mediated dilation (FMD) in African Americans. A secondary purpose was to evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 36 publications
2
33
1
Order By: Relevance
“…Furthermore, we cannot fully rule out the possibility that the structural remodelling was negatively influenced by the resistance training, as the transfers between different exercises in the circuit may have decreased the overall workload. Previous studies have also observed that FMD is elevated after prolonged (3 months) exercise training in type 2 diabetes patients (Okada et al 2010) and sedentary middle-aged subjects (Babbitt et al 2013). Furthermore, subjects with established coronary heart disease (Ades et al 2011) show no larger increase in vascular function after prolonged exercise training than studies adopting a 4-8 week training protocol, providing some support for our findings that the initial improvement in vascular function remains when continuing exercise training.…”
Section: Discussionsupporting
confidence: 84%
“…Furthermore, we cannot fully rule out the possibility that the structural remodelling was negatively influenced by the resistance training, as the transfers between different exercises in the circuit may have decreased the overall workload. Previous studies have also observed that FMD is elevated after prolonged (3 months) exercise training in type 2 diabetes patients (Okada et al 2010) and sedentary middle-aged subjects (Babbitt et al 2013). Furthermore, subjects with established coronary heart disease (Ades et al 2011) show no larger increase in vascular function after prolonged exercise training than studies adopting a 4-8 week training protocol, providing some support for our findings that the initial improvement in vascular function remains when continuing exercise training.…”
Section: Discussionsupporting
confidence: 84%
“…EMPs were analyzed as previously reported 35 . Briefly, plasma samples were centrifuged twice for 1500g for 20 minutes at 24°C to obtain cell free plasma.…”
Section: Methodsmentioning
confidence: 99%
“…18 Briefly, plasma samples were centrifuged twice at 1500g for 20 minutes at 24°C to obtain cell free plasma. 100 µL of sample was then incubated with fluorochromelabeled antibodies and fixed with 93 µL of 10% formaldehyde followed by gentle agitation (500 RPM) for 20 minutes at 24°C.…”
Section: Endothelial Microparticle Analysismentioning
confidence: 99%